Technology Integration in EFL Language Teaching: The Benefits and Challenges - Sinarman Jaya; Susyla, Dian (Edu-Ling: Journal of English Education and Linguistics, 2024)
The integration of technology in the classrooms has advantages and disadvantages. This study aims at investigating the advantages and difficulties that teachers encounter when utilizing technology in teaching and learning activities. The study employed a descriptive qualitative design. The study highlights key benefits such as increased motivation, personalized learning, access to authentic materials, enhanced collaboration, improved feedback, flexibility, accessibility, and digital literacy growth. However, it also points out challenges like unequal digital skills, limited access to technology, language barriers, over-reliance on digital tools, technical issues, distractions, high costs, privacy concerns, cultural differences, and struggles with self-discipline and motivation. To ensure effective and equitable technology integration in EFL teaching, the findings stress the need for comprehensive strategies that maximize benefits while addressing challenges. Technology offers significant advantages, but it requires careful management to overcome its limitations. Schools should invest in resources and support systems, and teachers need proper training. Future research should explore best practices and develop targeted solutions to address these challenges and optimize technology use in EFL education.